2015
DOI: 10.1109/jphot.2015.2430012
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Broadly Tunable 3-<named-content content-type="math" xlink:type="simple"> <inline-formula> <tex-math notation="TeX">$\mu\hbox{m}$</tex-math></inline-formula></named-content> Fiber Laser for the Measurement of Optical Fiber Loss

Abstract: We demonstrate a Ho 3þ , Pr 3þ co-doped fluoride fiber laser that produces an output power of 7.2 W, a 150-nm tuning range, and a narrow linewidth of G 0:14 nm using a power-scalable Yb 3þ fiber-laser-pumped 1150-nm Raman fiber laser as the excitation source. The maximum output power is achieved at a slope efficiency of 29%, with wavelength tuning between 2825 and 2975 nm that overlaps with the OH absorption region in many mid-infrared transparent glasses. The system is used to provide accurate measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An 1150 nm Raman fiber laser with 110 W of output power was used to pump a Hodoped fiber laser to generate 42 W of output power near 2048 nm [146]. 1150 nm Raman fiber lasers have also been used to pump Ho-doped ZBLAN fibers to generate 3 μm fiber lasers [147,148].…”
Section: Raman Lasers For Optical Pumpingmentioning
confidence: 99%
“…An 1150 nm Raman fiber laser with 110 W of output power was used to pump a Hodoped fiber laser to generate 42 W of output power near 2048 nm [146]. 1150 nm Raman fiber lasers have also been used to pump Ho-doped ZBLAN fibers to generate 3 μm fiber lasers [147,148].…”
Section: Raman Lasers For Optical Pumpingmentioning
confidence: 99%
“…In [29], a Ho 3+ /Pr 3+ co-doped fluoride fiber laser with an output power of Ps = 7.2 W was demonstrated. It exhibited a slope efficiency of η = 29% and a wavelength tuning range Δλ between In addition to erbium, other dopants have been successfully employed.…”
Section: Fluoride Glassesmentioning
confidence: 99%
“…In 2009, Jackson reported a 2.86 µm Ho 3+ , Pr 3+ -codoped ZBLAN fiber laser by using a 1100 nm Yb 3+ -doped silica fiber laser as the pump source and the maximum output power was ~2.5 W [14]. In 2015, Crawford et al demonstrated a 7.2 W tunable Ho 3+ , Pr 3+codoped ZBLAN fiber laser with a 150-nm tuning range from 2825 to 2975 nm [15]. However, ZBLAN glasses have poor water resistance and thermal stability [16], and therefore it is still necessary to develop other glass hosts with high stability for constructing 2.9 µm fiber lasers.…”
Section: Introductionmentioning
confidence: 99%